The Rise of Malaysian Gastro Diplomacy: From Local Cuisine to the Global Cuisine - Tasha Ayu Shalihan Putri; Riski M Baskoro (AEGIS : Journal of International Relations, 2021)
The “Malaysia Kitchen for the World” campaign designed by the Malaysian government acts as a practical effort of gastro diplomacy that is rooted in the sphere of cultural diplomacy. Thus, the purpose of this research is to identify the implementation of the “Malaysia Kitchen for the World” campaign in the United Kingdom between 2010 and 2015 and to provide a detailed analysis using the theories of International Relations study, consisting of public diplomacy, cultural diplomacy, and gastro diplomacy. This study employs a qualitative method with a case study approach, using secondary sources focusing on journals, articles, and books followed by primary sources from MATRADE and Malaysian government official publications. The findings of this research are that Malaysian cuisine is an essential element for the Malaysian government for promoting Malaysia’s cultural richness, branding local business, and raising global awareness of Malaysian food in the international arena, particularly among British citizens.